TOLERANCE OF CARDIOVASCULAR SYSTEM TO PHYSICAL LOAD IN ADOLESCENTS, AGED 16-18, BORN FROM FATHERS-LIQUIDATORS OF THE CHERNOBYL DISASTER - Korenev, N.M.; Borisko, G.A.; Kostenko, T.A.; Aphanasyeva, O. A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The adaptation capabilities (reaction to physical stress load) of 98 children, aged 16-18, born from fathers, who took part in liquidation of the Chernobyl nuclear disaster, as compared with adaptability of 53 children from the families with no radiation risk have been studied. Heart rate, blood pressure and echocardiogemo-ynamic indices were registrated at rest, on the first, the third and the fifth minutes after physical stress load. The adolescents born from the father-liquidators revealed a reduced reaction level to physical load. We recommend careful organization of physical training for such children.